The Effect Of Abdominal Stretching Exercise On Reducing Dysminorrhoea Pain At STIKes As Syifa Female Students - Titin Patimah; Selvi Puspan Sari; Paramita Mustari; Sri Junita Simaremare (Jurnal EduHealth, 2023)
Dysmenorrhea or painful menstruation is a gynecological complaint that occurs due to an imbalance in the hormone progesterone, resulting in pain that is often experienced by women, especially teenagers. One action that can be taken to treat dysmenorrhea is abdominal stretching exercises. The aim of this research was to determine the effect of abdominal stretching exercise on reducing dysmenorrhea in female female students at STIKes As Syifa. This research method was preexperimental with a one group pre test - post test design involving 33 female students who experienced dysmenorrhea. Sampling used the Total Sampling technique with data collection using the abdominal stretching exercise SOP and a numeric rating scale to determine the scale of dysmenorrhea. The results of data analysis using the Wilcoxon test obtained p=0.000 with a significance level of α=0.05. This shows that there is an influence of abdominal stretching exercise on reducing dysmenorrhea in female students at STIKes As Syifa. Conclusion: Abdominal stretching exercise is an effective exercise to reduce the scale of dysmenorrhea in female students and can be done independently when female students experience dysmenorrhea.